IDDF2018-ABS-0070 The new insertion method of the trans-nasal ileus tube, the anterior balloon method, was applicable for the small bowel obstruction: a retrospective chart review of the 135 patients. (June 2018) - Yamaguchi, Daisuke; Ikeda, Kei; Takeuchi, Yuki; Kinoshita, Rikako; Morisaki, Tomohito; Ario, Keisuke; Tsunada, Seiji; Sakata, Yasuhisa; Fujimoto, Kazuma
Abstract : Background: The gastrointestinal decompression is the initial and effective therapeutic approach for the patients with small bowel obstruction. Our previous pilot case report using the newly developed trans-nasal ileus tube, the anterior balloon method, achieved effective decompression to the small bowel obstruction (Yamaguchi D, et al. Dig Endosc. 2018;30:120–121). The present pilot study was investigated the effectiveness of new insertion method of transnasal ileus tube for small bowel obstruction in around 100 patients. Methods: The anterior balloon method used the ileus tube of 300 cm length with two (anterior and posterior) balloons. After insertion of the tube into the duodenum, the anterior balloon was injected and suctioned repeatedly with 10 mL of air using the10 mL syringe until the ileus tube reached closer to the obstruction (figure 1). A total of 135 patients with small bowel obstruction treated from January 2011 to January 2018 were retrospectively reviewed. The patients were divided into two groups: those who used the new insertion method: anterior balloon method in 52 patients (ABM group) versus the ordinary insertion method in 82 patients (OIM group). The patient and causes of ileus; treatment outcomes; and adverse events were compared between the two groups. Results: The patient characteristics and symptoms on admission were not different between ABM and OIM group. Adhesive ileus was the main cause of ileus between two groups. The ABM group experienced significantly shorter insertion time (28.2±9.1 vs. 33.5±13.0 min; p=0.008) and significantly longer length of insertion tube (223.2±32.3 vs. 157.4±31.7 cm; p<0.001) compared with OIM group. And ABM group experienced significantly shorter time for relief of clinical symptoms. The mean duration of the overall insertion tube and restarting of the meals in ABM group were significantly shorter than in OIM group. There were no significant differences in adverse events between two groups. Conclusions: The anterior balloon method was shorter insertion time, longer length of the insertion tube and superior to the ordinary insertion method for improvement of clinical symptoms. The anterior balloon method is convenient and worthy to achieve decompression for patients with small bowel obstruction.